Qualitative and quantitative aspects of information processing in first psychosis: Latent class analyses in patients, at‐risk subjects, and controls. (7th November 2014) - van Tricht, Mirjam J.; Bour, Lo J.; Koelman, Johannes H. T. M.; Derks, Eske M.; Braff, David L.; de Wilde, Odette M.; Boerée, Thijs; Linszen, Don H.; de Haan, Lieuwe; Nieman, Dorien H.
Abstract: We aimed to determine profiles of information processing deficits in the pathway to first psychosis. Sixty‐one subjects at ultrahigh risk (UHR) for psychosis were assessed, of whom 18 converted to a first episode of psychosis (FEP) within the follow‐up period. Additionally, 47 FEP and 30 control subjects were included. Using 10 neurophysiological parameters associated with information processing, latent class analyses yielded three classes at baseline. Class membership was related to group status. Within the UHR sample, two classes were found. Transition to psychosis was nominally associated with class membership. Neurophysiological profiles were unstable over time, but associations between specific neurophysiological components at baseline and follow‐up were found. We conclude that certain constellations of neurophysiological variables aid in the differentiation between controls and patients in the prodrome and after first psychosis.